Tribologische Messungen am Gelenkknorpel: ein Prüfstand zur Messung der Reibungszahlen von Knorpel gegen Knorpel, Regeneraten und TE-Konstrukten und erste Ergebnisse - Schwarz, Markus; Schneider-Wald, Barbara Katharina; Krase, Anika; Richter, Wiltrud; Reisig, Gregor; Kreinest, Michael; Heute, Steffen; Pott, Peter Paul; Brade, Joachim; Schütte, Andy (Der Orthopäde, 2012)
Values for the friction coefficient of articular cartilage are given in ranges of percentage and lower and are calculated as a quotient of the friction force and the perpendicular loading force acting on it. Thus, a sophisticated system has to be provided for analysing the friction coefficient under different conditions in particular when cartilage should be coupled as friction partner. It is possible to deep-freeze articular cartilage before measuring the friction coefficient as the procedure has no influence on the results. The presented tribological system was able to distinguish between altered and native cartilage. Furthermore, tissue engineered constructs for cartilage repair were differentiated from native cartilage probes by their friction coefficient. In conclusion a tribological equipment is presented to analyze the friction coefficient of articular cartilage, in vivo generated cartilage regenerates and in vitro tissue engineered constructs regarding their biomechanical properties for quality assessment.